2011
DOI: 10.1088/1478-3975/8/1/015009
|View full text |Cite
|
Sign up to set email alerts
|

The role of the cytoskeleton in cellular force generation in 2D and 3D environments

Abstract: To adhere and migrate, cells generate forces through the cytoskeleton that are transmitted to the surrounding matrix. While cellular force generation has been studied on 2D substrates, less is known about cytoskeletal-mediated traction forces of cells embedded in more in vivo-like 3D matrices. Recent studies have revealed important differences between the cytoskeletal structure, adhesion, and migration of cells in 2D and 3D. Because the cytoskeleton mediates force, we sought to directly compare the role of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
133
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 29 publications
(47 reference statements)
6
133
1
Order By: Relevance
“…Previous studies have found that nocodazole-induced depolymerization of microtubules disrupts tubulin polarity and cell-generated forces [44], and results in decreased migration velocity in cell-derived matrix [40]. In our assays, destabilization of microtubules resulted in significant cell rounding ( figure 5), but we did not find any general trend on how nocodazole treatment affected the migration speed of the cancer cells (figure 4c).…”
Section: Nocodazolecontrasting
confidence: 55%
“…Previous studies have found that nocodazole-induced depolymerization of microtubules disrupts tubulin polarity and cell-generated forces [44], and results in decreased migration velocity in cell-derived matrix [40]. In our assays, destabilization of microtubules resulted in significant cell rounding ( figure 5), but we did not find any general trend on how nocodazole treatment affected the migration speed of the cancer cells (figure 4c).…”
Section: Nocodazolecontrasting
confidence: 55%
“…In parallel, a link between microtubules and 3D matrix contraction by invasive mesenchymal cells was described in studies that used collagen gels (Bell et al, 1979;Kolodney and Wysolmerski, 1992;Kraning-Rush et al, 2011). Microtubules are required to generate wide-range traction forces in adhesive and elongated cells, such as mesenchymal cells cultured in 3D matrices (Kraning-Rush et al, 2011). This might not only reflect the impact of microtubules on the regulation of adhesion and contractility, but also point to a mechanical function.…”
Section: Microtubules In Cell Mechanics In a 3d Matrixmentioning
confidence: 97%
“…A mechanical role for microtubules in cell shape was suggested in early studies (Brown et al, 1996;Dennerll et al, 1988;Janmey et al, 1991;Rudolph and Woodward, 1978;Tomasek and Hay, 1984). In parallel, a link between microtubules and 3D matrix contraction by invasive mesenchymal cells was described in studies that used collagen gels (Bell et al, 1979;Kolodney and Wysolmerski, 1992;Kraning-Rush et al, 2011). Microtubules are required to generate wide-range traction forces in adhesive and elongated cells, such as mesenchymal cells cultured in 3D matrices (Kraning-Rush et al, 2011).…”
Section: Microtubules In Cell Mechanics In a 3d Matrixmentioning
confidence: 99%
“…Nevertheless, these biological matrices are still used today, as a qualitative measurement of cell traction force generation can sometimes be sufficient. For example, Kraning-Rush et al showed that contractility inhibition abrogates traction force generation in both 2D and 3D, demonstrating that cytoskeletal contractility is similarly important for traction force generation in 2D and 3D [90]. Other users have modified this strategy to quantify forces underlying tissue morphogenesis, where fluorescent deformable microdroplets are functionalized with adhesive ligands and embedded inside embryonic tissue matrices [91].…”
Section: Three-dimensional Traction Force Quantificationmentioning
confidence: 99%